An Efficient Method for Choosing Digital Cluster Size in Ultralow Latency Networks. (4th October 2021) - Paramonov, Alexander; Khayyat, Mashael; Chistova, Natalia; Muthanna, Ammar; Elgendy, Ibrahim A.; Koucheryavy, Andrey; Abd El-Latif, Ahmed A.
Abstract : The paper proposes a solution to the problem of choosing the size of a cluster in an ultralow latency network. This work is aimed at designing a method for choosing the size of the digital cluster in an ultralow latency network taking into account the lengths of connecting lines. If the linear dimension calculation is based only on the latency requirements without specifics of building the communication line, it negatively affects timing characteristics. This paper shows the method taking into account the communication line features and basing on the fractal dimension estimation of the road network. The proposed method could be used in planning and designing networks with ultralow latencies. Finally, a numerical experiment was carried out, based on the data of electronic maps, which showed that the assessment of the fractal dimension of roads in the network's service area makes it possible to increase the accuracy of the size of the formed cluster. Moreover, the proposed method can allow you to reduce the error in estimating the length of connecting lines, which without using it can be on average about 30%.